Effects of mescaline and its derivative N-[3,4,5-trimethoxyphenylethyl]-aziridine on the spatial orientation of rats in a T-maze - Koupilová, M; Herink, J (Physiologia Bohemoslovaca, 1989)
The central effect of mescaline and of its derivative N-[3,4,5- trimethoxyphenylethyl]-aziridine (FAZ) after their stereotaxic administration into the lateral ventricle of the brain was studied in behavioural experiments on rats. The effect of the two substances was tested by a method studying memory elicitation in response to appetitive motivation in a multiple T-maze. The results show that both substances worsened the behaviour in question. The negative effect of mescaline (lengthening of the time of passage through the maze) was manifested both immediately and several weeks after a single dose. FAZ likewise worsened the test reaction, but its effect was less pronounced than that of mescaline.
Keywords: inbrední kmeny potkanů; Behavior, Animal; Rats, Inbred Strains; Rats; prostorové chování; Memory; Injections, Intraventricular; aziridiny; mužské pohlaví; orientace; Orientation; krysa rodu Rattus; paměť; meskalin; zvířata; injekce intraventrikulární; Aziridines; Spatial Behavior; Mescaline; chování zvířat; Male; Animals